Experimental study on mechanical and durability properties of concrete incorporating various polyvinyl alcohol fiber lengths and dosages - Chen, W.; Wen, Y. (Materiales de Construcción, 2024)
To inquire about the properties of concrete reinforced with polyvinyl alcohol (PVA) fiber (various fiber lengths and dosages), different experimental tests including mechanical property, cracking resistance, and chloride resistance were investigated. The overall performance of PVA fiber-reinforced concrete (FRC) was innovatively analyzed integrating mechanical indicators and crack resistance parameters. Furthermore, nuclear magnetic resonance (NMR) and scanning electron microscope (SEM) were selected to analyze the causes and mechanisms underlying the alterations in the performance of PVA-FRC. The experimental results demonstrate that the flexural strength, the crack resistance characteristic and chloride ion penetration resistance of PVA-FRC are significantly improved compared to ordinary concrete. Increasing fiber length plays a key role in flexural strength, compared with fiber dosage. Considering both mechanical properties and durability, PVA-FRC containing 0.25% volume fraction of 12 mm PVA fibers (F12-0.25) demonstrated optimal performance.